2004
DOI: 10.1215/s1152851703000231
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 1p, 19q, 9p, and 10q as prognostic markers for high-grade astrocytomas using fluorescence in situ hybridization on tissue microarrays from Radiation Therapy Oncology Group trials

Abstract: Survival periods vary considerably for patients with high-grade astrocytomas, and reliable prognostic markers are not currently available. We therefore investigated whether genetic losses from chromosomes 1p, 19q, 9p, or 10q were associated with survival in 89 high-grade astrocytomas using tissue microarrays (TMAs) derived from Radiation Therapy Oncology Group clinical trials. Cases included 15 anaplastic astrocytomas (AAs) and 74 glioblastomas (GBMs) selected on the basis of survival times significantly short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 29 publications
4
44
1
2
Order By: Relevance
“…10 In astrocytomas (grade II/III), LOH 1p and 19q is reported to range from 0 to 17%. 11 The current study revealed isolated 19q and combined 1p/19q LOH in 17.6% of DA, similar to the Western literature. LOH 1p/19q was encountered in a solitary case of AA, which could perhaps be attributed to the small sample size.…”
Section: Discussionsupporting
confidence: 89%
“…10 In astrocytomas (grade II/III), LOH 1p and 19q is reported to range from 0 to 17%. 11 The current study revealed isolated 19q and combined 1p/19q LOH in 17.6% of DA, similar to the Western literature. LOH 1p/19q was encountered in a solitary case of AA, which could perhaps be attributed to the small sample size.…”
Section: Discussionsupporting
confidence: 89%
“…3,24,26 In contrast, loss of 19q has been established to be a hallmark of glioblastomas that may develop through a secondary multistep transformation process, and this abnormality was associated with long-term survival. 3,16,24,26 Nevertheless, various aberrations of chromosome 19 were found in the small minority of tumors from our current series, suggesting that these molecular alterations play no significant role in the evolution of pediatric glioblastomas, as well as codeletion of 1p/19q loci that was identified only in one tumor specimen.…”
Section: Discussionmentioning
confidence: 53%
“…[16][17][18][19][20] In the current study, we applied FISH technique for molecular profiling of pediatric glioblastomas, keeping in the mind its applicability to paraffin-embedded specimens and the presence of well-established criteria for reproducible results interpretation. To the best of our knowledge, this is a first FISH analysis of a representative cohort of pediatric glioblastomas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations